Declining Prevalence of Human Immunodeficiency Virus (HIV)–Associated Neurocognitive Disorders in Recent Years and Associated Factors in a Large Cohort of Antiretroviral Therapy–Treated Individuals With HIV. (19th August 2022) - Mastrorosa, Ilaria; Pinnetti, Carmela; Brita, Anna Clelia; Mondi, Annalisa; Lorenzini, Patrizia; Del Duca, Giulia; Vergori, Alessandra; Mazzotta, Valentina; Gagliardini, Roberta; Camici, Marta; De Zottis, Federico; Fusto, Marisa; et al.
Abstract: Background: HIV-associated neurocognitive disorders (HAND) have been suggested as persistent even with effective antiretroviral therapy (ART). Aims were to evaluate HAND prevalence and associated factors, in a large cohort of people-with-HIV (PWH). Methods: ART-treated PWH, underwent a neuropsychological examination through a battery of 12 tests exploring 5 different domains, between 2009 and 2020, were included in this cross-sectional analysis. HAND were classified according to Frascati's criteria. Participants were defined as complaining or not-complaining if a cognitive complaint was reported or not. Chi-square for trend and multivariable logistic regression were fitted. Results: Overall, 1424 PWH were enrolled during four three-years periods. HAND prevalence was 24%; among complainers (572/1424), it was 38%, higher than among not-complainers (15%). Over the study period, a decreasing HAND prevalence was found in the entire population ( P < 0.001) and in complaining ( P < 0.001); in not-complaining it remained stable ( P = 0.182). Factors associated with HAND were older age, lower educational level, lower current CD4 + T-cell count and HCV co-infection. Compared to nonnucleoside reverse transcriptase inhibitors, receiving dual and integrase strand transfer inhibitor (INSTI)-based therapies was associated with a decreased risk of HAND, as well as being tested in more recent years. Conclusions: In this large cohort of ART-treated PWH, mostly virologically suppressed, a remarkable decreasing HAND prevalence was observed. Besides HIV- and patient-related factors, the reduced risk of HAND found with dual and INSTI-based regimens along with a more recent ART initiation, could suggest a potential role of new treatment strategies in this decline, due to their greater virologic efficacy and better tolerability. Abstract : Over the last decade, a decreasing prevalence of human immunodeficiency virus (HIV)–associated neurocognitive disorders (HAND) was found. The asymptomatic form remained prevalent compared with symptomatic stages. A reduced risk for HAND was observed with dual and integrase strand transfer inhibitor–based regimens, along with more recent initiation of antiretroviral therapy.